A Resilience-Based Intervention to Mitigate the Effect of HIV-Related Stigma: Protocol for a Stepped Wedge Cluster Randomized Trial - Li, Xiaoming; Qiao, Shan; Yang, Xueying; Harrison, Sayward E.; Tam, Cheuk Chi; Shen, Zhiyong; Zhou, Yuejiao (Frontiers in Public Health, 2022)
Background. Despite decades of global efforts to tackle HIV-related stigma, previous interventions designed to reduce stigma have had limited effects that were typically in the small-to-moderate range. The knowledge gaps and challenges for combating HIV-related stigma are rooted both in the complexity of the stigma and in the limitations of current conceptualizations of stigma reduction efforts. Recent research has shown the promise of resilience-based approaches that focus on the development of strengths, competencies, resources, and capacities of people living with HIV (PLWH) and their key supporting systems (e.g., family members and healthcare providers) to prevent, reduce, and mitigate the negative effects of stigma. However, the resilience-based approach, while hypothesized, has rarely been empirically tested in large intervention trials, especially in resource-limited settings. Methods. In this study, we propose to develop, implement, and evaluate a theory-guided, multilevel, multimodal resilience-based intervention via a stepped wedge cluster randomized trial among 800 PLWH and their biological or surrogate family members, as well as 320 healthcare providers in Guangxi, China with a longitudinal follow-up period of 36 months at 6-month intervals. The primary outcome will be viral suppression and the intermediate outcomes will include perceived stress and medication adherence of PLWH as well as resilience measures at the level of the individual, the family, and the healthcare system. Discussion. The proposed study will be one of the first large-scale efforts to examine whether resilience among PLWH can be fostered and sustained through a multilevel and multi-component HIV-related stigma intervention and whether a resilience-based intervention can improve clinical outcomes and quality of HIV care among PLWH in a low-resource setting. If efficacious, the intervention components could be tailored to other groups of PLWH and adapted for other low- and middle-income countries.